FR2.1: Is Forum Theatre a Gender Transformative Tool: Experience from Bangladesh - Haque, S.M. Faridul (WorldFish, 2022)
Social norms, values, and practices in most cases create barriers for women to be involved in income-generating activities. The aquaculture sector is one of the examples of such a field where women's limited participation is determined by a set of socio-cultural factors. Forum theatre could be an effective tool to break these barriers due to its participatory and bottom-up nature. This paper focuses on the effectiveness of forum theatre as a tool of a gender transformative approach. It examines the efficiency of forum theatre to enable people to identify and adopt alternatives to the existing gender-biased practices. A qualitative study was conducted in March 2022 with 30 men and 30 women in the Northwestern part of Bangladesh. The findings show that forum theatre creates an enabling environment of peer learning and hence offers the opportunity for people to accept new practices. This article illustrates the importance of forum theatre, as a gender transformative tool to ensure women's participation and benefit from the aquaculture sector.